Ian Jackson's Sphincter Pharyngoplasty. (May 2021) - Mittermiller, Paul A.; Staffenberg, David A.
Abstract : Abstract: Velopharyngeal insufficiency (VPI) after cleft palate repair remains an intriguing problem for the cleft surgeon. While other options for the treatment of VPI, in many ways the sphincter pharyngoplasty has become a reliable and satisfying operation. When the applied to the properly selected patient, it rearranges the palatopharyngeus muscles to provide dynamic closure of the newly created central velopharngeal port. The dynamic action is particularly satisfying to the surgeon. The surgery evolved in part because of the dedication and creativity of Dr Ian Jackson who's description is closest to the design used today. In his memory we felt it fitting to review Dr Jackson's involvement with the surgery over the decades as well as include our own thoughts on the advantages of the procedure.